2009
DOI: 10.4161/derm.1.2.7811
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal surface lipids

Abstract: A layer of lipids, which are of both sebaceous and keratinocyte origin, covers the surface of the skin. The apparent composition of surface lipids varies depending on the selected method of sampling. Lipids produced by the epidermal cells are an insignificant fraction of the total extractable surface lipid on areas rich in sebaceous glands. Due to the holocrine activity of the sebaceous gland, its product of secretion (sebum) is eventually released to the surface of the skin and coats the fur as well. Lipids o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
230
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(246 citation statements)
references
References 58 publications
16
230
0
Order By: Relevance
“…Recently, Adeyo et al (46) found lipid droplet accumulation with a deficiency of SLURP1, a secreted peptide of keratinocytes. Triglyceride hydrolysis in the epidermal keratinocytes is known to be important for producing the lipids for lamellar bodies, which play key roles in skin barrier function (47)(48)(49)(50). We were able to identify lamellar bodies in the keratinocytes of Lmna Ϫ/Ϫ Lmnb1 ⌬/⌬ Lmnb2 ⌬/⌬ mice, but we suspect that they were ineffective in establishing a normal skin barrier, given the disorganization in the upper layers of the epidermis.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, Adeyo et al (46) found lipid droplet accumulation with a deficiency of SLURP1, a secreted peptide of keratinocytes. Triglyceride hydrolysis in the epidermal keratinocytes is known to be important for producing the lipids for lamellar bodies, which play key roles in skin barrier function (47)(48)(49)(50). We were able to identify lamellar bodies in the keratinocytes of Lmna Ϫ/Ϫ Lmnb1 ⌬/⌬ Lmnb2 ⌬/⌬ mice, but we suspect that they were ineffective in establishing a normal skin barrier, given the disorganization in the upper layers of the epidermis.…”
Section: Discussionmentioning
confidence: 78%
“…We observed that the amount of collagen was substantially lower in nonmelanoma skin cancer lesions as compared to normal skin. This could be explained by the breakdown of collagen in dermis due to the role metalloproteinases (MMP) play in degrading collagen and prohibiting procollagen biosynthesis [35]. The thickening of the epidermis also leads to reduced collagen signal collected by the probe.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal lipids act like a cement to fill the spaces between the cells. The major constituents of sebaceous lipids are triglycerides (triolein), wax esters and squalene, while the epidermal lipids are a mixture of ceramides, free fatty acids and cholesterol [35,36]. Ceramide is an important epidermal surface lipid as it composes almost half of the SC lipids [32].…”
Section: Lipidsmentioning
confidence: 99%
“…Sebum is a group of complex lipids including triglycerides and fatty acid breakdown products, wax esters, squalene, cholesterol esters and cholesterol [9][10][11][12][13] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%